Islamic Cosmology Between Medieval Philosophy and Modern Science: The Persistence of the Qur’anic Worldview - Tiar Anwar Bachtiar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
As Islam spread to various regions, especially to Europe, the Islamic cosmological worldview—whose foundation is the revelation of Allah (Swt.)—had to encounter already established cosmological ideas. In Medieval Europe, the dominant Christian cosmological view was in fact heavily influenced by Greek philosophy, particularly the ideas of Plato and Aristotle. Later, in the modern period in Europe, the dominance of philosophy was gradually replaced by secular science, which tended toward ateistic perspectives. How, then, did Islam respond to these intellectual currents, both the constructions of Greek philosophy and secular science? Was Islam influenced by philosophy and science in such a way that it altered its cosmological worldview, or did it instead utilize them to reaffirm Islamic cosmology? This paper, which analyzes relevant texts using the approach of intellectual history, finds that Islamic cosmology—grounded in the revelation of Allah (Swt.)—has been successfully engaged in dialogue by Muslim thinkers to face the challenges posed by both traditions. They employed the same instruments of argumentation, namely philosophy and science, harmonizing them with divine revelation so that the dialogue remained balanced. This is demonstrated in the works of Muslim thinkers such as Ibn Sina, Al-Ghazali, Hossein Nasr, Naquib Al-Attas, and others. They successfully used philosophy and science to defend an Islamic cosmology based on the revelation of Allah (Swt.). The principles of Islamic cosmology have never changed, even when encountering philosophy and science.